THE EFFECT OF ABDOMINAL STRETCHING EXERCISES ON REDUCING DYSMENORRHEA PAIN IN ADOLESCENTS IN PERTUMBUKAN VILLAGE WAMPU SUBDISTRICT LANGKAT REGENCY NORTH SUMATERA PROVINCE IN 2024 - Dewi, Mahyar Fitri; Imran Saputra Surbakti; Herna Rinayanti Manurung; Asnita Sinaga; Bunga Aulia Dwi Fattahillah; Salsabila; Tetti Situmorang (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
ABSTRACT Introduction: Quality of life for adolescents is a positive assessment within the life cycle, reflected in their satisfaction with themselves, particularly in terms of both physical and psychosocial health, including a positive self-image. Reproductive health in women is an essential component, as the female reproductive system is susceptible to various disorders that may lead to reproductive health problems. One of the most common reproductive health issues is dysmenorrhea, which can significantly affect quality of life, daily activities, and academic performance. Objective: to analyze the effect of abdominal stretching exercises on reducing dysmenorrhea pain in adolescents in Pertumbukan Village, Wampu Subdistrict, Langkat Regency, North Sumatra Province in 2024. Method: This research is a quantitative study using a quasi-experimental design with a non-equivalent control group design. The approach applied was the two-group pretest and posttest method. The sampling technique used was non-probability sampling with purposive sampling. Results: showed that the group given abdominal stretching exercises experienced a significant reduction in dysmenorrhea pain (p-value = 0.00), while the group that did not receive the intervention had no significant change (p-value = 0.1000). Conclusion: Based on these findings, it can be concluded that abdominal stretching exercises have a significant effect on reducing dysmenorrhea pain in adolescents in Pertumbukan Village, Wampu Subdistrict, Langkat Regency, North Sumatra Province, in 2024.